Electric Mars: The first direct measurement of an upper limit for the Martian "polar wind" electric potential. Issue 21 (5th November 2015) - Collinson, Glyn; Mitchell, David; Glocer, Alex; Grebowsky, Joseph; Peterson, W. K.; Connerney, Jack; Andersson, Laila; Espley, Jared; Mazelle, Christian; Sauvaud, Jean‐André; Fedorov, Andrei; Ma, Yingjuan; et al.
Abstract: An important mechanism in the generation of polar wind outflow is the ambipolar electric potential which assists ions in overcoming gravity and is a key mechanism for Terrestrial ionospheric escape. At Mars, open field lines are not confined to the poles, and outflow of ionospheric electrons is observed far into the tail. It has thus been hypothesized that a similar electric potential may be present at Mars, contributing to global ionospheric loss. However, no direct measurements of this potential have been made. In this pilot study, we examine photoelectron spectra measured by the Solar Wind Electron Analyzer instrument on the NASA Mars Atmosphere and Volatile EvolutioN (MAVEN) Mars Scout to put an initial upper bound on the total potential drop in the ionosphere of Mars of Φ ♂ ≾ ⊥ 2 V, with the possibility of a further ≾ 4.5 V potential drop above this in the magnetotail. If the total potential drop was close to the upper limit, then strong outflows of major ionospheric species (H +, O +, and O 2 + ) would be expected. However, if most of the potential drop is confined below the spacecraft, as expected by current theory, then such a potential would not be sufficient on its own to accelerate O 2 + to escape velocities, but would be sufficient for lighter ions. However, any potential would contribute to atmospheric loss through the enhancement of Jeans escape. Key Points: We put the first upper limit on the magnitude of the "polar wind" like parallel electric field The strength of this electric field is <2 V in the ionosphere This field is too weak to accelerate O 2 + (the main ionospheric species) to escape velocities